The Common Security Interests of Japan, The United States, and NATO, Joint Working Group of the Atlantic Council of the United States & The Research Institute for Peace and Security, Tokyo. Cambridge, Massachusetts: Ballinger Publishing, 1981, 232 - Egelund, Niels (Politica, 1982)
-